1994
DOI: 10.1038/bjc.1994.161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eicosapentaenoic acid and other fatty acids on the growth in vitro of human pancreatic cancer cell lines

Abstract: Summary A number of polyunsaturated fatty acids have been shown to inhibit the growth of malignant cells in vitro. To investigate whether fatty acids modify the growth of human pancreatic cancer, lauric, stearic, palmitic, oleic, linoleic, alpha-linolenic, gamma-linolenic, arachidonic, docosahexaenoic and eicosapentaenoic (EPA) acids were each incubated with the cells lines MIA PaCa-2, PANC-1 and CFPAC at concentrations ranging from 1.25 JAM to 5011M and the effect of each fatty acid on cell growth was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
80
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 22 publications
4
80
1
Order By: Relevance
“…EPA has previously been shown to inhibit the growth of pancreactic cancer cell lines (Falconer et al, 1994). In the current study, we have observed similar inhibitory effects with EPA supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EPA has previously been shown to inhibit the growth of pancreactic cancer cell lines (Falconer et al, 1994). In the current study, we have observed similar inhibitory effects with EPA supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effects of indomethacin on various in vitro models show that it can either stimulate or inhibit tumour cell proliferation (Buckman et al, 1991;Fulton, 1984;Rose and Connolly, 1990;Bayer et al, 1979;Hial et al, 1977). Other studies have suggested that increased lipid peroxidation may be an important cause of cytotoxicity associated with n-3 PUFAs but a definite role has not been established (Falconer et al, 1994;Lystad et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies of pancreatic cancer indicate that while dietary fat per se does not cause pancreatic cancer (Roebuck, 1992), individual polyunsaturated fatty acids (FAs), but not monounsaturated or saturated FAs, have an inhibitory effect on the growth of human pancreatic cancer cell lines (Falconer et al, 1994), suggesting that an association between dietary fats and pancreatic cancer may depend on the level of specific FA intake.…”
mentioning
confidence: 99%